United States oil policy, 1890-1964: business and government in twentieth century America - Nash, Gerald D. ([Pittsburgh, Pa.] University of Pittsburgh Press, 1968)
This book provides a history of the oil policy in the United States of America between 1890 to 1964. It describes the growth of cooperation as a prime characteristics of public policy in the petroleum industry.
Includes bibliographical references and index.
lje 24/1/19
Loans
Keywords: Petroleum industry and trade; Oil and Gas; Energy policy; United States